The Effect of Bentonite (BNTN) Nanoclays with Multiple Weight Proportions on the Mechanical Properties of Polyacrylamide (PAM) Composites - Hilal, Raghad Hamid (Al-Nahrain Journal for Engineering Sciences, 2022)
The research includes studying the mechanical properties of BNTN/PAM nanocomposites under static and dynamic conditions. The BNTN/PAM nanocomposites were prepared with different weight fractions (0, 20%, 40%, 50% and 60%) by utilizing ball milling technique. Tensile strength, Charpy impact and Shore A hardness were performed to verify any improvements in these mechanical properties of nanocomposites. The results showed significant improvements in tensile, Charpy impact, Shore A hardness properties of nanocomposites at 50% weight fraction by approximately 335%, 1422%, 63% respectively. These results started decreasing after addition of 60% of nanoclays content to PAM composites. This mechanism indicates that the percentage of weight content of BNTN could affect the mechanical properties of nanocomposites.